Chapter 16 Between Adversariness and Compromise A Rhetorical Analysis of Greek Political Discourse in Times of Crisis - Tseronis, Assimakis (Taylor & Francis, 2023)
The chapter reviews the extent to which contemporary Greek scholarship in humanities and social sciences makes use of rhetorical categories as relevant descriptive and analytical tools. It proposes revisiting two classical rhetorical concepts, namely topoi and endoxa, in order to illustrate their descriptive and explanatory potential for the analysis of political discourse characterized by adversariness, polyphony, and the need to create communion. To illustrate this theoretical and methodological proposal, two fragments of parliamentary discourse are analysed by combining the insights of Pragma-Dialectics and the Argumentum Model of Topics. The fragments are from the speeches that the government and opposition leaders held during the parliamentary debate on the signing of the first memorandum of understanding between Greece and the 'troika' of the European Commission, the European Central Bank, and the International Monetary Fund in May 2010.